Biotrophic and saprophytic fungi from the Rhodocybe-Clitopilus clade (Entolomataceae): two new species and one new record in subtropical China - Sipeng Jian; Xia Chen; Tianwei Yang; Xinjing Xu; Feng Gao; Yiwei Fang; Jing Liu; Chunxia Zhang (MycoKeys)
This study proposes two new species and a new record in the Rhodocybe-Clitopilus clade, based on comprehensive morphological and molecular analyses. The nuc rDNA internal transcribed spacer region ITS1-5.8S-ITS2 (ITS), the large subunit ribosomal RNA gene (LSU), the RNA polymerase II second largest subunit (RPB2) and the translation elongation factor 1-alpha gene (TEF1), were employed to elucidate the relationships of Clitopilus and Rhodocybe. The first species, Clitopilus parasiticus, is capable of infecting the leaves of host plants in the genera Dryopteris and Oplismenus, exhibiting typical biotrophic behaviour while also demonstrating saprophytic growth on soil. Intraspecific comparisons were conducted, examining environmental factors as well as macro- and microscopic characteristics amongst individuals found on different plant hosts. Furthermore, this study reports the new saprophytic species, Rhodocybe zijinshanensis and provides a detailed description of Clitopilus baronii, a newly-recorded species in China.